2013
DOI: 10.1016/j.jacc.2013.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Right Ventricular Function, Body Composition, and Prognosis in Advanced Heart Failure

Abstract: RV dysfunction and cardiac cachexia often coexist, have additive adverse impact, and might be mechanistically interrelated. Wasting of fat but not of lean mass was predictive of adverse outcome, suggesting that fat loss is either a surrogate of enhanced catabolism or adipose tissue is cardioprotective in the context of HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 47 publications
8
109
1
1
Order By: Relevance
“…Some authors described the positive correlations between adiponectin, severity of HF, and NT-proBNP [7,21], whereas Melenovsky et al found an inverse relationship between plasma BNP and concentrations of leptin in HF patients [26]. We observed no correlation with leptin or adiponectin concentration.…”
Section: Prace Oryginalnecontrasting
confidence: 75%
“…Some authors described the positive correlations between adiponectin, severity of HF, and NT-proBNP [7,21], whereas Melenovsky et al found an inverse relationship between plasma BNP and concentrations of leptin in HF patients [26]. We observed no correlation with leptin or adiponectin concentration.…”
Section: Prace Oryginalnecontrasting
confidence: 75%
“…Interestingly, RV systolic dysfunction was a significant predictor of mortality even after adjustment for age and PASP in a Cox regression model (Hazard Ratio=1.4, P=0.02; Figure 5). Further evidence has recently been brought by Melenovsky et al 45 reporting a worse RV function and prognosis in PH-HFpEF associated with atrial fibrillation.…”
Section: Guazzi Pulmonary Hypertension In Diastolic Heart Failure 371mentioning
confidence: 94%
“…6 Studies investigating the pattern of right heart function and geometry in PH-HFpEF are summarized in Table 1. [9][10][11]14,15,21,[40][41][42][43][44][45] In a report by Puwanant et al, 11 RV dysfunction, assessed by RV fractional area and tissue Doppler S prime, was not uncommon in patients with HFpEF although in a milder degree compared with HFrEF. Similar findings were reported by looking at RV global longitudinal early diastolic strain rate and systolic RV global longitudinal systolic strain.…”
Section: Guazzi Pulmonary Hypertension In Diastolic Heart Failure 371mentioning
confidence: 99%
“…62 However, evidence from prospective studies indicates that the decrease in fat mass precedes that of lean mass. [63][64][65] Moreover, individuals with cardiac cachexia have exceedingly high circulating levels of BNP, including a significant fraction of incompletely processed N-terminal pro-BNP.…”
Section: Cardiac Cachexiamentioning
confidence: 99%